When Does a Calcium Score Equates to Secondary Prevention?: Insights From the Multinational CONFIRM Registry - Budoff, Matthew J.; Kinninger, April; Gransar, Heidi; Achenbach, Stephan; Al-Mallah, Mouaz; Bax, Jeroen J.; Berman, Daniel S.; Cademartiri, Filippo; Callister, Tracy Q.; Chang, Hyuk Jae; Chow, Benjamin J.W.; Cury, Ricardo C.; et al. (Journal of the American College of Cardiology : Cardiovascular imaging, 2023)
Background: Elevated coronary artery calcium (CAC) scores in subjects without prior atherosclerotic cardiovascular disease (ASCVD) have been shown to be associated with increased cardiovascular risk. Objectives: The authors sought to determine at what level individuals with elevated CAC scores who have not had an ASCVD event should be treated as aggressively for cardiovascular risk factors as patients who have already survived an ASCVD event. Methods: The authors performed a cohort study comparing event rates of patients with established ASVCD to event rates in persons with no history of ASCVD and known calcium scores to ascertain at what level elevated CAC scores equate to risk associated with existing ASCVD. In the multinational CONFIRM (Coronary CT Angiography Evaluation for Clinical Outcomes: An International Multicenter) registry, the authors compared ASCVD event rates in persons without a history of myocardial infarction (MI) or revascularization (as categorized on CAC scores) to event rates in those with established ASCVD. They identified 4,511 individuals without known coronary artery disease (CAC) who were compared to 438 individuals with established ASCVD. CAC was categorized as 0, 1 to 100, 101 to 300, and >300. Cumulative major adverse cardiovascular events (MACE), MACE plus late revascularization, MI, and all-cause mortality incidence was assessed using the Kaplan-Meier method for persons with no ASCVD history by CAC level and persons with established ASCVD. Cox proportional hazards regression analysis was used to calculate HRs with 95% CIs, which were adjusted for traditional cardiovascular risk factors. Results: The mean age was 57.6 ± 12.4 years (56% male). In total, 442 of 4,949 (9%) patients experienced MACEs over a median follow-up of 4 years (IQR: 1.7-5.7 years). Incident MACEs increased with higher CAC scores, with the highest rates observed with CAC score >300 and in those with prior ASCVD. All-cause mortality, MACEs, MACE + late revascularization, and MI event rates were not statistically significantly different in those with CAC >300 compared with established ASCVD (all P > 0.05). Persons with a CAC score <300 had substantially lower event rates. Conclusions: Patients with CAC scores >300 are at an equivalent risk of MACE and its components as those treated for established ASCVD. This observation, that those with CAC >300 have event rates comparable to those with established ASCVD, supplies important background for further study related to secondary prevention treatment targets in subjects without prior ASCVD with elevated CAC. Understanding the CAC scores that are associated with ASCVD risk equivalent to stable secondary prevention populations may be important for guiding the intensity of preventive approaches more broadly.
CRIS-Team Scopus Importer:2023-08-11
Keywords: coronary artery disease; coronary calcium; coronary computed tomography angiography; prognosis